ANALYSIS OF ISLAMIC LAW ON THE REQUIREMENTS OF A MAXIMUM OF 10% OF NON-HALAL INCOME IN THE ISSUANCE OF THE SHARIA SECURITIES LIST IN INDONESIA - Frizka Oktaviani (JIL : Journal of Indonesian Law, 2021)
The Financial Services Authority (OJK) as the authorized institution to supervise and make regulations on economic activities in Indonesia has issued OJK Regulation Number 35/POJK.04/2017 about the criteria and issuance of the Sharia Securities List. One of the criteria is that it is permissible for companies with a maximum of 10% of non-halal income to be included in sharia securities. This causes the mixing of halal and haram assets. This study is aimed at finding out how the criteria for the issuance of the Sharia Securities List are in the Financial Services Authority Regulation Number 35/POJK.04/2017 and why the Financial Services Authority determines the non-halal income requirement of a maximum of 10% in the criteria for the issuance of the Sharia Securities List and how the analysis of Islamic law on it in the criteria for the issuance of the Sharia Securities List. This is a qualitative research with the type of library research. The results of this study conclude that the criteria for the issuance of the Sharia Securities List in the Financial Services Authority Regulation Number 35 of 2017 are divided into qualitative and quantitative criteria. This rule is enforced because of Indonesia's economic conditions that it is impossible to get issuers who are not involved with interest in their business activities. The analysis of Islamic law on the rules of a maximum of 10% of non-halal income does not violate the provisions of fiqh muamalah.